Roles of Surfactants in Oriented Immobilization of Cellulase on Nanocarriers and Multiphase Hydrolysis System - Wang, Zhiquan; Fan, Chunzhen; Zheng, Xiangyong; Jin, Zhan; Bei, Ke; Zhao, Min; Kong, Hainan (Frontiers in Chemistry, 2022)
Surfactants, especially non-ionic surfactants, play an important role in the preparation of nanocarriers and can also promote the enzymatic hydrolysis of lignocellulose. A broad overview of the current status of surfactants on the immobilization of cellulase is provided in this review. In addition, the restricting factors in cellulase immobilization in the complex multiphase hydrolysis system are discussed, including the carrier structure characteristics, solid-solid contact obstacles, external diffusion resistance, limited recycling frequency, and nonproductive combination of enzyme active centers. Furthermore, promising prospects of cellulase-oriented immobilization are proposed, including the hydrophilic-hydrophobic interaction of surfactants and cellulase in the oil-water reaction system, the reversed micelle system of surfactants, and the possible oriented immobilization mechanism.